1999
DOI: 10.1143/jjap.38.l492
|View full text |Cite
|
Sign up to set email alerts
|

GaN on Si Substrate with AlGaN/AlN Intermediate Layer

Abstract: A single crystal GaN thin film was successfully grown on a Si (111) substrate by means of atmospheric pressure metalorganic chemical vapor deposition. Though there is a large difference in thermal expansion coefficients between GaN and Si, an intermediate layer consisting of AlN and AlGaN improved the quality of GaN on Si and reduced meltback etching during growth. Pits and cracks were not observed on the substrate and a mirror-like surface was obtained. The full-width at half maximum (FWHM) of the double-crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
122
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 14 publications
(8 reference statements)
1
122
0
1
Order By: Relevance
“…25 A high-temperature AlGaN/AlN nucleation layer of thickness about 110 nm, was grown to prevent the diffusion of Ga into the Si substrate, 9 which was followed by the growth of 135 pairs of AlGaN/AlN strained layer superlattice (SLSs). 10 The SLS buffer was used to control the strain balance on the large-area wafer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A high-temperature AlGaN/AlN nucleation layer of thickness about 110 nm, was grown to prevent the diffusion of Ga into the Si substrate, 9 which was followed by the growth of 135 pairs of AlGaN/AlN strained layer superlattice (SLSs). 10 The SLS buffer was used to control the strain balance on the large-area wafer.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] GaN growth on a Si substrate is one of the most useful methods for providing large-area GaN wafers at a low cost. [4][5][6][7][8] As aresult of several breakthroughs, 9,10 an AlGaN/GaN HEMT on Si demonstrated a breakdown voltage of over 1400 V. 10 Unfortunately, the large lattice and thermal expansion mismatches between Si and GaN produce high-density dislocations in a GaN layer. [11][12][13] Decreasing the dislocation density in a GaN layer has been a major issue because the dislocations are considered to deteriorate the reliability and life of devices.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the GaN layer growth, 80 nm thick AlN buffer layers were deposited on SBS substrates in order to prevent meltback etching [12]. For GaN and AlN growth, trimethylgallium (TMG), trimethylaluminum (TMA), and NH 3 were used as reactant precursors and H 2 as a carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Prior to the GaN layer growth, 80 nm thick AlN buffer layers were deposited on the SBS substrates in order to prevent meltback etching. [12,13] The typical thickness of GaN epilayers after growing for 80 min was 1.4 lm. Field-emission-gun scanning electron microscopy (FEG-SEM) and optical microscopy were employed to investigate the surface morphology of the GaN epilayers on SBS substrates at different growth stages.…”
mentioning
confidence: 99%
“…The Si substrate has the advantages of low cost, large area availability, and reasonable thermal conductivity over sapphire and SiC. We have reported that an intermediate layer with high thermal stability is required to prevent meltback etching and succeeded in growing flat GaN films on Si [1,2]. However, due to the large lattice and thermal mismatches, it is still difficult to obtain high-quality GaN films on Si.…”
Section: Introductionmentioning
confidence: 99%